Part I: Ni-Co alloy foils electrodeposited using ionic liquids - Omar, Inam M. A. (Elsevier B.V., 2020)
The Ni-Co alloy co-electrodeposit from a sulfate bath including two new ionic liquids 1-methyl-3-(2-oxo-2-((2,4,5 trifluorophenyl) amino) ethyl)-1H-imidazol-3-ium iodide [MOFIM]I and 1-(4-fluorobenzyl)-3-(4-phenoxybutyl) imidazol-3-ium bromide [FPIM]Br as additives was characterized using the SEM, EDS, EDS mapping, XRD, AFM and microhardness measurement techniques. The resultant surface morphologies in acidic sulfate baths on a copper substrate demonstrated that both the [MOFIM]I and [FPIM]Br additives served as effective leveling agents. The Ni-Co alloy co-deposit morphology in the [MOFIM]I bath was more enhanced (non-grained coating, Ra of 28 nm and Rt of 35.5 nm) than that in the [FPIM]Br bath (grain size 225 nm, Ra of 51. 1 nm and Rt of 65.7 nm) owing to the molecular structure. The co-deposition of Co and Ni from the acidic baths was of the anomalous type. Moreover, the anomalous behavior of the Ni-Co co-deposition was alleviated after [MOFIM]I and [FPIM]Br were introduced in the bath. To determine the optimal bath conditions, the cathodic current efficiency (CCE%) value was calculated during the Ni-Co alloy co-electrodeposition process under three different compositions and different operating conditions. Under the composition of Ni 70% and Co 30% (Ni70%-Co30% alloy deposit), the CCE% values increased considerably, with maximum values of 99.8% and 97.07% in the baths including [MOFIM]I and [FPIM]Br, respectively.